Native American and indigenous peoples' world of work - Stone, Dianna L.; Lukaszewski, Kimberly M.; Murray, Brian (Emerald Publishing Limited, 2025)
This book contains an Open Access Chapter. The UN estimates that there are approximately 476 million indigenous people around the world, and there are 1.8 million Native Americans in the USA. These individuals face recurring challenges with high rates of unemployment, poverty, unequal access to health care, low educational levels, and housing and food insecurity. They also face cultural dominance by one or more European countries, the confiscation of indigenous lands, environmental degradation, racism, higher suicide rates, shorter longevity rates, and countless indignities. Another one of the biggest challenges facing Native Americans and indigenous people is that they often experience unfair discrimination in the employment process and exclusion from work organizations, which perpetuates their high rates of poverty. Despite these problems, there has been little or no research on Native American work issues in human resource management or related fields. Native American and Indigenous Peoples' World of Work aims to fill these research gaps. It considers the factors that affect unfair discrimination, racism, and the exclusion of indigenous people in work organizations; highlights the benefits of including indigenous people in organizations; develops a better understanding of indigenous people's work values, job choices, and reward preferences so organizations can attract and retain them; and offers directions for future research and practice on the plight of indigenous people in organizations. Along with The Dignity of Native Americans and Indigenous Peoples' Experiences at Work these volumes are unique in being the first titles on Native American or indigenous work issues, and many authors are indigenous people.
Includes index.
Keywords: Indigenous peoples -- Employment.; Racism in the workplace.; Diversity in the workplace.; Business & Economics -- Diversity & Inclusion.; Diversity, equality and inclusion in the workplace.; elektronické knihy; electronic books